Application of carrot powder in preparation of low-fat frozen yoghurt - Kugashiya, Dhaval; Dharaiya, Chetan N; Mallik, Jarita; Rathwa, Rachana (Indian Journal of Dairy Science, 2023)
Low-fat frozen yoghurt was prepared using carrot powder as one of the ingredients. Response surface methodology (RSM) was used to optimize the level of carrot powder, stabilizer-emulsifier mixture and sugar. The responses were sensory attributes such as flavour, body and texture, melting quality, colour and appearance and total score as well as physical attributes like melted quantity and overrun. Based on the output, RSM suggested the rate of addition of carrot powder, stabilizer-emulsifier mixture and sugar to be 3.93%, 0.41% and 14.30% respectively. The experimental frozen yoghurt was prepared as per the suggestions from RSM and compared with control low-fat frozen yoghurt where carrot powder was replaced with vanilla flavour. The experimental frozen yoghurt was statistically similar in terms of compositional parameters except moisture and carbohydrate content while the experimental sample was superior to control sample in terms of sensory attributes. Aerobic plate count of both the samples were statistically similar while coliform as well as yeast and mold were absent in the product.